Concepción del desarrollo de habilidades comunicativas en la formación inicial del maestro - Morales Pupo, M. Sc. Blanca Rosa; Marrero Aballe, M. Sc. Yudy Yadira; Caballero Velázquez, Dr. C. Elizabeth (Transformación, 2024)
Objective: The impact of communication in the educational environment is a permanent object of scientific research. This article aims at analyzing the didactic approach to communicative skills in primary teachers’ education view from a professional perspective.Methods: Documentary review, theoretical methods of analysis and synthesis, and induction and deduction, together observation were used to collect data and modeling the professional approach to communication.Results: A pedagogical conception is proposed for improving communicative abilities development in educational an environment, as a component of teachers’ education.Conclusions: A pedagogical professional approach to communicative skills favors strengthens teachers’ performance and the systemic and comprehensive nature of this process in primary teachers’ education.Keywords: language instruction, language skill, basic skills, teacher education.
Keywords: language instruction; language skill; basic skills; teacher education